2013
DOI: 10.33225/jbse/13.12.497
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Views Regarding Homeworks Given in Science Courses

Abstract: The aim of this study was to explore parents’ opinions about homework assignments given in science and technology courses. The sample of the study was composed of 764 parents who reside in the city of Osmaniye in Turkey. The data were collected by a “Parent Homework Scale” developed by the researcher. The instrument includes three subscales; function, attitude and behavior. U-Test and H-Test were employed to identify any difference among variables. The findings showed that there was no significant difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Most of the studies showed that students', teachers', and parents' views about homework assignments were multidimensional with respect to some variables. For example, Deveci and Onder (2015) found that female students' function scores were higher than those of male students when the scores for the function, attitude, and behavior subscales were investigated by gender. Besides this, students who allotted more time for reading, homework, and research scored higher on each subscale than those who did not.…”
Section: Theme 1: Students' Teachers' and Parents' Views About Homewo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies showed that students', teachers', and parents' views about homework assignments were multidimensional with respect to some variables. For example, Deveci and Onder (2015) found that female students' function scores were higher than those of male students when the scores for the function, attitude, and behavior subscales were investigated by gender. Besides this, students who allotted more time for reading, homework, and research scored higher on each subscale than those who did not.…”
Section: Theme 1: Students' Teachers' and Parents' Views About Homewo...mentioning
confidence: 99%
“…The purpose of this study is to investigate the students' perspectives on the assigned homework in science and technology courses through a qualitative search. Deveci and Onder (2015) Inquiring into the opinions of the students on the homework given in science classes was the goal of the current study. The purpose of this study was to learn what parents thought about the homework that was assigned in science and technology courses.…”
Section: Theme 1: Students' Teachers' and Parents' Views About Homewo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Kelley and Knowles (2016) argue for an integrated STEM subject. Most studies report positive results about entrepreneurship being integrated with science education (Deveci & Cepni, 2017) and the European Commission (2015, p. 9) states that one objective of science education is: 'Strengthening connections and synergies between science, creativity, entrepreneurship and innovation'. Deveci and Cepni (2017, p. 127) argue that 'scientific entrepreneurship means the process of producing innovative, science-based products based on the ability to forecast a new product that is not on the market'.…”
Section: Entrepreneurship Within Stem Educationmentioning
confidence: 99%
“…Universities promote entrepreneurship by providing guidelines and strategies for entrepreneurship education (Saldarriaga & Guzm{n, 2018). Entrepreneurship requires a skill set that can be acquired by students and benefits them (Deveci & Çepni, 2017). Accordingly, universities have implemented teaching methodologies, business models and practices to generate business ideas (Saldarriaga & Guzm{n, 2018).…”
Section: Introductionmentioning
confidence: 99%